Pertencimento Grená: um estudo sobre os vínculos comunicacionais dos torcedores da desportiva ferroviária no Espírito Santo - Guanandy, Leandro Nossa (2019)
In Espírito Santo state, the majority of the population do not support local club. Historically, the club that had the most achievements in the state scenario attracted the largest number of local fans, including Desportiva Ferroviária. This work aims to study how to build belonging community through the support of Desportiva Ferroviária in Espírito Santo. Using qualitative research, semi structured questionnaires were applied to ten club fans. The collected statements are analyzed in order to evaluate: (i) the motivations to become a supporter of Desportiva Ferroviária; (ii) the meaning of being a supporter of Desportiva Ferroviária; (iii) the fans' ownership relationship with the club and the local community; and (iv) the main sources of information fans use to search for club content. In addition to the questionnaires, the records collected by the author in the Espírito Santo stands were used from the perspective of the participating observer. The results show that the main motivations for choosing Desportiva Ferroviária involve connection with Espírito Santo state and identification with the club, as well as the team's past success and history. It is noteworthy here that, for the choice, there is great relevance of territory and identity. Regarding the meaning of being a supporter of Desportiva Ferroviária, or being a “grená”, it is noteworthy that the fans relate the fans to the fact that they are capixabas (Espírito Santo natives), reinforcing the role of territoriality, as well as a form of resistance. In addition, a particularity of the fans in contrast to the fans of major national clubs, is the identification by the fans themselves of the role of club collaborator, not only spectator. The results reinforce the fans' relationship of belonging to the club and the community, as they recognize themselves as community leaders. Finally, the findings reinforce the role of social network and WhatsApp groups as the main source of information about the club, mainly due to the low adherence of traditional media to local football coverage.